Clinical association of body symptoms and primary dysmenorrhea among young and middle-aged women: an observational study - Tseng, Tzyy-Guey; Kuan, Che-Yen; Lo, Yun-Ping; Chuang, Yun-Shiuan; Lee, Chun-Ying; Lin, Yi-Ting; Shyu, Ing-Luen; Wu, Ming-Tsang; Tai, Chi-Jung (Frontiers in Medicine, 2025)
BackgroundThe mechanism of primary dysmenorrhea remains unraveled. Body symptoms not related to menstrual cycle may indicate the potential mechanism of primary dysmenorrhea, albeit the association has not been proven. Furthermore, we hypothesize that the cumulative burden of these symptoms may influence the incidence of primary dysmenorrhea. Therefore, we aim to design a study to identify bodily symptoms potentially related to primary dysmenorrhea and test the hypothesis in understanding and managing primary dysmenorrhea.MethodsA total of 3,140 female participants aged 30–50 years were enrolled from the Taiwan Biobank. Stepwise logistic regression was used to select potential body symptoms associated with primary dysmenorrhea from a training dataset. Selected body symptoms were validated in a test dataset. Female participants without dysmenorrhea in the baseline survey were divided into two groups (with and without body symptoms) in a baseline survey. Cox regression and Kaplan-Meier survival analyses were used to evaluate the risk of incident dysmenorrhea.ResultsWomen with body symptoms such as cold extremities (adjusted odds ratio [AdjOR], 1.53, 95% confidence interval [CI], 1.12–2.21), dull abdominal pain (AdjOR, 1.45, 95% CI, 1.03–2.04), and edema (AdjOR, 1.43, 95% CI, 1.02–1.99) were significantly associated with dysmenorrhea. Women with the three body symptoms had a significantly higher risk of dysmenorrhea (adjusted hazard ratio, 2.74, 95%CI, 1.18–6.31; log-rank test, p = 0.0017) than those without body symptoms. Trend analysis showed that the risk of dysmenorrhea increased with the number of body symptoms (p-trend = 0.025).ConclusionThis study identified cold extremities, dull abdominal pain, and edema as predictors of primary dysmenorrhea, with their accumulation associated with a higher risk of developing dysmenorrhea. We propose that further research explore pharmacological and non-pharmacological interventions targeting these symptoms, as they may provide long-term benefits in the management of primary dysmenorrhea.